Clinical Management Of Leucorrhea(Swetapradara) By Daruharidra With And Without Dhatakyadi Taila - VEENA JAWALE,; BHEEMSHETTY S. PATIL, (International Journal of Pharma and Bio Sciences, 2015)
A cross sectional study of 30 women of age group 20- 40 years was conducted to asses Clinical Management of Leucorrhea (Swetapradara) by Daruharidra with and without Dhatakyadi Taila. Subjects were divided into two groups namely Group I (n=15) patients who were administered only Daruharidra preparation of 10 ml, orally BID. for period of 30 days. Group II (n= 15) patients who were administered Daruhardra preparation of 10 ml orally BID. for period of 30 days and Dhatakyadi Taila in vagina for 10 days. Amount of discharge was graded and depending upon that effect of these drugs was observed. Incidence according to age, socioeconomic status and mental stress and strain was recorded. We have found significant changes among the group I (p<0.05*) and group II (p<0.05*). Leucorrhea though a symptom causing considerable discomfort is curable and preventable. Daruharidra and Dhatakyadi Tail are found good, natural and cost effective therapeutics in the control of Leucorrhea